Literature Study of Stock Investment Risk Analysis for Beginner Investors - Sugangga, Rayyan; Rahman, Iradah; Makaryanawati, Makaryanawati (Universitas Islam Kadiri, 2024)
Awareness of investment has been owned by all parties, including young people who unfortunately still do not understand the risks of investment. This can certainly have a negative impact that is far from the expectations or objectives of the investment itself. This article was compiled using a literature review based on the Google Scholar database for the period 2014-2024, with one of the objectives to study the risks often experienced by novice investors. The results of the literature review show that investment decisions whose decision making is ideally rational, but often become irrational and this condition is very relevant to various theories such as the theory of Efficient Market Hypothesis (EMH), the theory of Behavioral Finance, the Theory of Planned Behavior.